Całożyciowe uczenie się jako idea edukacyjna, polityka, strategie działań i zmieniający się krajobraz edukacyjny rzeczywistości - Solarczyk-Ambrozik, Ewa (Studia Edukacyjne, 2018)
The idea of lifelong learning has appeared in 1920’s, situating on the background of the phenomena of adult education, which, since it emergence, have been a long way – as shall be defined – from the socialization of the masses to the empowerment of individuals, and the prospect of such changes is included into a peculiar continuum – between industrialization and urbanization, and the knowledge society. Nowadays the problem of lifelong learning goes far beyond the traditionally perceived adult education. Inscribing itself into the global educational discourse becomes its essential issue – it refers to the questions of educational possibilities and opportunities in the different socio-cultural contexts. It dominates the discussions on adult education, vocational training and higher education, providing a theoretical framework for the development of relevant policy and action strategies, but in addition it plays a crucial role in economic debates on labour market, quality, capacity, sustainable development, learning in organizations and – importantly – it also appears in non-education-related debates including such issues as: social exclusion, unemployment, environmental protection, active citizenship and health. The phenomenon of lifelong learning allows to respond to such conceptual categories as flexibility and uncertainty. As a result of technological advances, competition creates the need for flexibility which in case of learners is, in the one hand, recognised as emancipation, and in the other, as a threat to individuals enable to meet the new requirements associated with individual responsibility for the course of the educational path. Alongside opinions presenting anti-institutional interpretation of lifelong learning, the „supply” of an institutional offer of adult education is raised. The conclusions of the presented analyses results in showing lifelong learning as a phenomenon, which is not unambiguously evaluated, since it may by understood as a the purpose, a process, an effect, a form of self-realization, a socio-cultural constraint, and at least as an important field of educational reality in the word of new challenges.